2021
DOI: 10.3390/f12081035
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Patterns of ‘Ōhi‘a Mortality Associated with Rapid ‘Ōhi‘a Death and Ungulate Presence

Abstract: Effective forest management, particularly during forest disturbance events, requires timely and accurate monitoring information at appropriate spatial scales. In Hawai‘i, widespread ‘ōhi‘a (Metrosideros polymorpha Gaud.) mortality associated with introduced fungal pathogens affects forest stands across the archipelago, further impacting native ecosystems already under threat from invasive species. Here, we share results from an integrated monitoring program based on high resolution (<5 cm) aerial imagery, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…In Hawaiʻi, these wounds may provide infection courts for Ceratocystis ‐laced frass dispersed by wind, rain and soil movement. Perroy et al (2021) reported that the presence of ungulates (i.e., pigs and cattle) in previously animal‐free areas was associated with rapid increases in ROD mortality. Direct transmission of pathogen‐infested frass by animal bark‐stripping, rooting and rubbing, or by insect vectors carrying the pathogens, have not been verified, but these alternative vector pathways are currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Hawaiʻi, these wounds may provide infection courts for Ceratocystis ‐laced frass dispersed by wind, rain and soil movement. Perroy et al (2021) reported that the presence of ungulates (i.e., pigs and cattle) in previously animal‐free areas was associated with rapid increases in ROD mortality. Direct transmission of pathogen‐infested frass by animal bark‐stripping, rooting and rubbing, or by insect vectors carrying the pathogens, have not been verified, but these alternative vector pathways are currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, high wind events can damage branches and stems, simultaneously affecting large numbers of trees across the landscape. In Hawaiʻi, feral ungulates can rub, chew or strip patches of bark off M. polymorpha, and their presence in forests is strongly associated with elevated ROD mortality (Perroy et al, 2021). Prior studies with other hosts have demonstrated that Ceratocystis platani can travel between trees through functional root grafts (Tsopelas et al, 2017).…”
mentioning
confidence: 99%
“…Humans can also create infection courts when they wound ʻōhiʻa. Similarly, evidence suggests that feral ungulates are suspected of creating wounds on ʻōhiʻa trees, leading to increased mortality rates of ʻōhiʻa in stands where ungulates are present versus ungulate-free stands (Perroy et al 2021). Understanding how these potential transport and wounding mechanisms contribute to the spread of the ROD pathogens is integral for the long-term management of Hawaiʻi's native forests.…”
Section: Dispersal and Transmission Of The Rod Pathogensmentioning
confidence: 99%
“…Since there is limited ability to control windblown frass, efforts are also being made to reduce injuries to trees that can subsequently become infected. Fencing more pristine forests and removing feral ungulates such as cattle, goats, sheep, and pigs can reduce injury to trees, and fenced and protected forests have shown much lower levels of disease than forests with high populations of feral animals (Perroy et al 2021). Natural ʻōhiʻa regeneration is occurring at higher elevation forests (above 1,000 m), and seedlings seem less susceptible to the diseases than larger trees (R. F. Hughes pers comm).…”
Section: Overall Management Strategy For Rodmentioning
confidence: 99%
“…Based on limited data, Pimental (2007) estimated that wild pigs cost the United States $1.5 billion annually as a result of damages caused by wild pigs and the costs to control these wild populations. Their ability to carry and transmit pathogens also poses a considerable and yet vastly understudied threat to humans, livestock, and resident flora and fauna (Bevins et al 2014;Perroy et al 2021).…”
Section: Introductionmentioning
confidence: 99%